Determinan Kejadian Penyakit Infeksi Saluran Pernapasan Akut pada Balita di Wilayah Kerja Puskesmas 7 Ulu Palembang - Putri, Ririn Noviyanti; Putri, Meliya; Muslimin, Muslimin; Sitindaon, Rina SE; Ernia, Rima (Universitas Batanghari Jambi, 2024)
Currently, ISPA disease in Palembang City is still one of the highest causes of death among children under five. Risk factors associated with the incidence of ARI are extrinsic and intrinsic factors. The aim of this research was to determine the relationship between exclusive breastfeeding, maternal knowledge, smoking habits, nutritional status and the incidence of ISPA in toddlers in the working area of the 7 Ulu Palembang Community Health Center. This research is analytical with a cross sectional design. The population in this study were mothers with toddlers aged 24 - 59 months with a sample size of 66 people. The sampling technique in this research is purposive sampling. The results of the research show that there is a relationship between exclusive breastfeeding, maternal knowledge, smoking habits, nutritional status and the incidence of ARI in toddlers in the working area of the 7 Ulu Palembang Community Health Center. It is hoped that the end of this research will be an illustration for the community health center to be able to further improve health services and be more active in providing counseling and education regarding ISPA in toddlers.